Point Prevalence Multicenter Survey of Antimicrobial Utilization in Russian Hospitals: the Results of GLOBAL-PPS 2017 - S. A. Rachina; Yu. A. Belkova; R. S. Kozlov; A. S. Anikeev; A. V. Tolpygo; E. G. Burasova; L. G. Ezhova; E. V. Elokhina; B. M. Mishchenko; O. G. Ni; G. A. Penzhoian; E. E. Sventitskaia; et al. (Антибиотики и Химиотерапия, 2020)
The results of Global Point Prevalence Survey of Antimicrobial Consumption and Resistance (GLOBAL-PPS) project conducted in 7 multi-field hospitals in different cities of Russia (Krasnodar, Moscow, Omsk, Smolensk, Tomsk, Ulan-Ude) during the period from September to November 2017 are presented. Case records of patients who received systemic antimicrobial agents for the treatment or prevention of infections were analyzed. Local practices of antimicrobials administration were evaluated with help of quality indicators defined in GLOBAL-PPS study protocol. Common mistakes requiring a prompt intervention included low adherence to clinical guidelines, absence of stop/review dates in the medical records, extended duration of surgical prophylaxis, III generation cephalosporin's overuse for prophylaxis and treatment and low frequency of therapy based on microbiological data.Our data provide the basis for the development of appropriate antimicrobial stewardship programs tailored according to local practices for each multi-field hospital in the project.